Tanggungjawab Pelaku Usaha Rumah Makan Padang Terhadap Perolehan Sertifikasi Halal di Kota Pekanbaru: Responsibilities of Padang Restaurant Business Actors for Obtaining Halal Certification in Pekanbaru City - Muhammad Yogi Riazmi Putra; Hasnati Hasnati; Yeni Triana Triana (Universitas Medan Area, 2022)
This writing is entitled the responsibility of business actors for Padang restaurants to obtain halal certification, it is necessary to pay attention to the safety of food products that are now freely circulating. Not only in terms of health but also guarantee the halal of the product. Although there have been various regulations made by the Government of Indonesia, but still found the existence foods that do not have label certified. The aim of this writing is to find out how the protection of consumer laws and legal consequences received by business actors related to the distribution of food products that are not halal certified. In this paper, the authors use normative research methods. Which examine and analyze the legislation and the linkage of legal principles relating to the labeling of halal food products between Law no. 8 of 1999 about protection of consumer with Law no. 33 of 2014 about Halal Product Guarantee. The results of the analysis obtained are the protection of consumer law against non halal certified food products arranged in Law no. 8 of 1999 about protection of consumer, Law no. 33 of 2014 about Halal Product Guarantee, and Government Regulation Number 69 years 1999 on about Label and Food advertising, while the legal effect that the business actor receives on the distribution of non halal certified food products is by imposing administrative punishment and criminal penalty.